Roles of Chondroitin Sulfate Proteoglycans as Regulators of Skeletal Development - Schwartz, Nancy B.; Domowicz, Miriam S. (Frontiers in Cell and Developmental Biology, 2022)
The extracellular matrix (ECM) is critically important for most cellular processes including differentiation, morphogenesis, growth, survival and regeneration. The interplay between cells and the ECM often involves bidirectional signaling between ECM components and small molecules, i.e., growth factors, morphogens, hormones, etc., that regulate critical life processes. The ECM provides biochemical and contextual information by binding, storing, and releasing the bioactive signaling molecules, and/or mechanical information that signals from the cell membrane integrins through the cytoskeleton to the nucleus, thereby influencing cell phenotypes. Using these dynamic, reciprocal processes, cells can also remodel and reshape the ECM by degrading and re-assembling it, thereby sculpting their environments. In this review, we summarize the role of chondroitin sulfate proteoglycans as regulators of cell and tissue development using the skeletal growth plate model, with an emphasis on use of naturally occurring, or created mutants to decipher the role of proteoglycan components in signaling paradigms.